Global Television: An Introduction - Barker, Chris (Wiley-Blackwell, 1997)
This text provides readers with useful summaries and evaluations of key arguments relating to the development of television as an industry across the globe and its potential cultural impact. There is a continual insistence in the book on the need to connect issues of industry with those of culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Television, Globalization and Cultural Identities - Barker, Chris (Open University Press, 1999)
* Are cultural identities socially constructed? * How are race, nation, sex and gender constructed and represented on television? * What is the impact of globalization on television and cultural identities? This introductory text examines issues of television and cultural identities in the context of globalization. It is a wide-ranging volume, exploring many of the central cultural issues in contemporary cultural studies, such as media, globalization, language, gender, ethnicity, cultural politics and identity - perhaps the topic of cultural studies over the past decade. At the core of the book are two critical arguments - that television is a proliferating resource for the construction of cultural identity, and that cultural identity is not a fixed essential 'thing' but a contingent social construction to which language is central. The book will be essential reading for undergraduate and postgraduate courses on television and cultural identities in the fields of cultural studies, communications, media studies and sociology, with a wider appeal to those with an interest in the television industry. Key concepts are introduced and explained for those new to cultural studies, whilst debates are extended and enriched for those already familiar with them. The text is well structured, links the vocabularies of media studies and cultural studies, and is supported by original case study material.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé